Polyamines: Bio-Molecules with Diverse Functions in Plant and Human Health and Disease - Handa, Avtar K.; Fatima, Tahira; Mattoo, Autar K. (Frontiers in Chemistry, 2018)
Biogenic amines – polyamines (PAs), particularly putrescine, spermidine and spermine (and thermospermine) are ubiquitous in all living cells. Their indispensable roles in many biochemical and physiological processes are becoming commonly known, including promoters of plant life and differential roles in human health and disease. PAs positively impact cellular functions in plants – exemplified by increasing longevity, reviving physiological memory, enhancing carbon and nitrogen resource allocation/signaling, as well as in plant development and responses to extreme environments. Thus, one or more PAs are commonly found in genomic and metabolomics studies using plants, particulary during different abiotic stresses. In humans, a general decline in PA levels with aging occurs parallel with some human health disorders. Also, high PA dose is detrimental to patients suffering from cancer, aging, innate immunity and cognitive impairment during Alzheimer and Parkinson diseases. A dichotomy exists in that while PAs may increase longevity and reduce some age-associated cardiovascular diseases, in disease conditions involving higher cellular proliferation, their intake has negative consequences. Thus, it is essential that PA levels be rigorously quantified in edible plant sources as well as in dietary meats. Such a database can be a guide for medical experts in order to recommend which foods/meats a patient may consume and which ones to avoid. Accordingly, designing both high and low polyamine diets for human consumption are in vogue, particularly in medical conditions where PA intake may be detrimental, for instance, cancer patients. In this review, literature data has been collated for the levels of the three main PAs, putrescine, spermidine and spermine, in different edible sources - vegetables, fruits, cereals, nuts, meat, sea food, cheese, milk and eggs. Based on our analysis of vast literature, the effects of PAs in human/animal health fall into two broad, Yang and Yin, categories: beneficial for the physiological processes in healthy cells and detrimental under pathological conditions.